Sustainable material as a column filler in soft clay bed reinforced with encased column: numerical analysis - Srijan; A. K. Gupta (Scientific Reports)
Abstract Soil reinforcement is one of the techniques used to enhance the engineer characteristics of the soil. Various techniques can be employed to stabilise problematic soils, such as soft clay. These include the utilisation of portland cement, lime, fly ash, ground freezing, jet grouting, prefabricated vertical drains, and thermal approaches. Similarly, stone columns are one of the most popular methods for enhancing soil and have been adopted across the world to enhance bearing capacity and minimise total and differential settlements of structures built on soft clay. Additionally stone columns serving as vertical drains, thus accelerate consolidation process. But with higher demand of construction material and depletion of natural resources, there is a need of using waste products as a substitute to existing construction materials. In this paper, manufacturing waste like steel slag is used as a sustainable material for column infill and can be affordable and also address the current environmental concern which by removing solid waste… A series of numerical investigation was carried out to study the various behavioural characteristics of virgin soft clay bed, clay bed installed with ordinary steel slag column and also with encased steel slag column. A comparison was made among all for studying the various parameters such as settlement, excess pore water pressure, stress concentration ratio & lateral deformation of columns.